2008
DOI: 10.1007/s00701-007-1400-1
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of vasopressin receptor antagonist OPC-31260 on experimental brain oedema induced by global cerebral ischaemia

Abstract: The effects of the non-peptide vasopressin V(2) receptor antagonist 5-dimethylamino-1-[4-(2-methylbenzoylamino)benzoyl]-2,3,4,5-tetrahydro-1H-benzazepine hydrochloride (OPC-31260) on the cerebral oedema induced by general cerebral hypoxia were studied in rats. The general cerebral hypoxia was produced by bilateral common carotid ligation in Sprague-Dawley rats of the CFY strain. By 6 h after the ligation, half of the rats had died, but the survival rate was significantly higher following OPC-31260 administrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 36 publications
2
10
0
Order By: Relevance
“…Brain edema formation predicts an unfavorable outcome in ICH[31]. Therefore, copeptin levels might reflect developing or existing brain edema and might therefore be helpful in identifying patients at risk for brain edema formation who could profit from therapeutic interventions, such as the administration of a vasopressin antagonist[28]. A limitation of our study was that we could not monitor brain edema formation and link it with copeptin values, because imaging studies of the brain were not routinely repeated.…”
Section: Discussionmentioning
confidence: 99%
“…Brain edema formation predicts an unfavorable outcome in ICH[31]. Therefore, copeptin levels might reflect developing or existing brain edema and might therefore be helpful in identifying patients at risk for brain edema formation who could profit from therapeutic interventions, such as the administration of a vasopressin antagonist[28]. A limitation of our study was that we could not monitor brain edema formation and link it with copeptin values, because imaging studies of the brain were not routinely repeated.…”
Section: Discussionmentioning
confidence: 99%
“…Levels are positively correlated with hematoma volume, death at 30 days following ICH, and poor functional outcome at 3 months as measured by the mRS and the Barthel Index [113]. Vasopressin inhibitors have been investigated as a potential therapeutic intervention [114].…”
Section: Othersmentioning
confidence: 99%
“…In one study, the V2 receptor was found to mediate a positive feedback loop for AVP release (Landgraf et al, ), suggesting clinical value of V2 antagonism in ceasing AVP‐mediated brain damage after brain injury. However, the opposite V2‐mediated negative feedback was suggested in several studies, showing that V2 antagonism with OPC‐31260 after subarachnoid hemorrhage or cerebral ischemia led to an enhancement in AVP levels (Laszlo et al, ; Molnar et al, ). These studies also opposed the notion described above that V2 antagonism provides no benefit after brain injury by indicating that V2 antagonism attenuates the accumulation of cerebral water content and cerebral sodium (Manaenko et al, ; Kleindienst et al, ).…”
Section: Antagonism Of Vasopressin Receptorsmentioning
confidence: 99%
“…When targeting vasopressin receptors for brain injury, V1a antagonism is crucial, inasmuch as the literature indicates a strong role of the V1a receptor in the pathogenesis of secondary brain damage after initial injury. However, mixed vasopressin antagonists may be of value in additionally targeting any potential V2‐mediated positive feedback to increase AVP expression after stroke (Landgraf et al, ; Laszlo et al, ; Molnar et al, ). Although the studies on mixed vasopressin receptor antagonists are limited, they reveal significant potential in vasopressin modulation for the future treatment of brain injuries and brain fluid disorders.…”
Section: Mixed Vasopressin Receptor Antagonismmentioning
confidence: 99%